(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Producing cooked and frozen crab requires cooking raw materials, which results in the loss of useful components and a decrease in the yield of the finished product. To reduce losses during the heat treatment of raw materials, water-binding food additives are usually used; however, in the case of crab, the process is hindered by the shell. The present research proposes a way to accelerate the process by ultrasound treatment, which provides a high diffusion rate of phosphates in the muscle tissue of the red king crab (Paralithodes camtschaticus) limbs. The potentially destructive effect of ultrasonic waves on the muscle tissue structure and on its beneficial components is compensated by the water-binding ability of phosphates, which is confirmed by the high quality of the final product. The proposed method was tested under production conditions, proving the possibility and feasibility of its use at fishing industry enterprises.